Effectiveness of Metabolite Substance Filtrates of Actinomycetes isolates from Kebun Raya Bogor against the growth of Escherichia coli, Pseudomonas aeruginosa and Salmonella typhi: In Vitro study - Muhammad Zaidan Tsani Ariandi; Meiskha Bahar; Hany Yusmaini; Fajriati Zulfa; Cut Fauziah; Andri Pramesyanti (Jurnal Biologi Tropis, 2021)
Actinomycetes are found in soils with loose, humus, dry characteristics and around plant roots. Actinomycetes produce secondary metabolite compounds as antibacterial. Escherichia coli, Pseudomonas aeruginosa and Salmonella typhi are Gram negative bacteria that can cause infection in humans. This study aims to determine the ability of the Actinomycetes metabolite filtrate from Bogor Botanical Gardens as an antibacterial agent against the growth of E. coli, P.aeruginosa and S. typhi in vitro. This study used an experimental design with samples of Actinomycetes isolats originating from the Bogor Botanical Gardens soil using the disc diffusion method on Muller Hinton Agar (MHA) media by looking at the clear zone of bacterial growth around the disc paper. Of the three concentration groups, namely 50%, 60%, and 70%, the largest average inhibition zone is found at a concentration of 70% with the average for the three test bacteria E. coli, P.aeruginosa and S. typhi respectively: 4.23 mm; 3.0 mm and 8.43 mm. The results of the Kruskal - Wallis test with p value = 0.01 showed that there was an effect of the Actinomycetes metabolite filtrate on the growth of the three tested bacteria as antibacterials.ÃÂ ÃÂ